To evaluate the change in release from solid dispersion using sodium lauryl sulfate and model drug sulfathiazole. (October 2013) - Dave, Rutesh H.; Patel, Hardikkumar H.; Donahue, Edward; Patel, Ashwinkumar D.
Abstract : The solubility of drugs remains one of the most challenging aspects of formulation development. There are numerous ways to improve the solubility of drugs amongst which the most promising strategy is solid dispersion. Different ratios of sulfathiazole: PVP-K29/32: sodium lauryl sulfate (SLS) were prepared (1:1:0.1, 1:1:0.5, 1:1:1) and various methods were employed to characterize the prepared solid dispersions, namely modulated differential scanning calorimeter, X-ray powder diffraction, Fourier Transformed Infrared Spectroscopy and dissolution studies. Lack of crystallinity was observed in internal and external systems suggesting a loss of crystallinity, whereas the physical mixtures showed a characteristic peak of sulfathiazole. In vitro dissolution results clearly showed that the incorporation of a relatively small amount of surfactants (5, 20 or 33% w/w) into a solid dispersion can improve its dissolution rates compared to binary solid dispersion (SD) alone and pure sulfathiazole. In all ratios solid dispersion internal shows a higher dissolution rate compared to a physical mixture and solid dispersion external which suggests that the way that the surfactant is incorporated into the solid dispersion plays an important role in changing the solubility of a drug. The solubilization mechanism is mainly responsible for this higher dissolution rate when we incorporate the SLS in SD.